The Chicano/Mexicano experience: a phenomenological investigation of accomplishment through the voices and essence of elderly Chicano/Mexicano former agricultural workers in northern Colorado - Treviño, Manuel, author; Lehmann, Jean P., advisor; Banning, James H., committee member; Granger, Ben P., committee member; Foster, Ann, committee member (Colorado State University. Libraries, 1999)
The purpose for this study was to investigate lessons learned by the Chicano/Mexicano experience. Specifically, this study explored the accomplishment of antecedent Chicano/Mexicano former Farmworkers in Northern Colorado. The journeys and experiences of these families served as the focal point for the study. This population was selected because of similarities with contemporary youth in areas of disenfranchisement and marginalization. The general questions that guided this study were as follows: Research Questions. 1. What was your family's journey during this era? 2. Why have you chosen this path? 3. What has your journey been like? 4. You have already survived this era—tell me about the journey? 5. How has life worked for you? How did you make it work? 6. From your journey, what would you recommend for young people? 7. What would you like to pass on to the next generation? 8. What were your strengths that held it all together? What issues got in the way? Qualitative methodology, specifically phenomenological investigation, served as the guiding path for the study. Personal interviews were the primary methods used for data collection. The purpose was to capture lessons learned and develop strategies for addressing perseverance and achievement of marginalized populations in contemporary school systems. The actuality that these predecessors persisted and addressed issues of racism, language barriers, and isolation through modified levels of assimilation and acculturation, and had positive outcomes, is paramount. The resolve summoned to persevere and develop is necessary knowledge for addressing marginalized populations. Families who met the selection criteria were integrated into the study as coresearchers. The selection criterion follows: 1. Arrival time to Northern Colorado: Mid part of twentieth century. 2. Age of participants: 70-92 years old. 3. Ethnicity: Chicano/Mexicano/Hispanic. 4. Longevity: Remained in the area, considered this area their home. 5. Bi-cultural: Mexican/Anglo. 6. Can operate independently in United States culture. 7. Gender: Male or female. 8. Speak English and Spanish. 9. Point of Departure: South Texas. The study found that co-researchers had taken similar paths toward achievement of positive outcomes. The findings revealed strategies distinguished as critical lessons learned for achievement. The outcomes shed light on experiences of marginalized and/or disenfranchised groups. Implications were interpreted as strategies that educational and human service systems could use to help with the engagement of students.
Keywords: bilingual education; multicultural education; minority and ethnic groups; sociology; gerontology